Faktor Sosial Budaya yang Memengaruhi Kesehatan Ibu dan Anak (Studi Etnografi) - Salsabila Salsabila; Zakiyatul Faizah; Budi Prasetyo (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
Maternal and child health as a key indicator of community welfare is measured by Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). The problem of maternal and child mortality is a problem that cannot be separated from the culture or behavior of the community itself. The social and cultural system in the community is an important consideration in health services that can be utilized more optimally. The purpose of this study was to determine what cultural factors affect the health of mothers and children. This research is a rapid ethnographic assessment procedure (REAP) with a qualitative approach. Sampling technique using snowball or chain referral sampling. It is carried out sequentially from one participant to another. Is a variation of the purposive sample. The number of respondents as many as 8 people who fit the inclusion criteria. The data shown were the result of indepth interviews and FGDs (Focus Group Discussion). This study resulted in findings about: (1) Kyai become community role models in responding to life's problems ranging from political choices to choices of access to health. (2) Women do not have sufficient full power or empower themselves to choose health services, especially during pregnancy and childbirth. (3) The element of belief inherited from generation to generation also forms the knowledge system of the Cibitung community. (4) The livelihood system of farm laborers as the main source of the economy in Cibitung. Keywords: Socio-Cultural, Ethnographic, Religious Systems, Kinship Systems, Knowledge Systems, Livelihood Systems